Last holiday [videorecording (DVD)] - Queen Latifah, 1970-; LL Cool J, 1968-; Depardieu, Gérard, 1948-; Hutton, Timothy, 1960- (Paramount Home Entertainment, 2017)
In this hilarious comedy, discover what happens when a woman finds out that her days are numbered. She throws caution to the wind to embark on a lifetime of fun in just a few weeks.